A Scoping Review of Recent Developments Linking Artificial Intelligence and Lifelong Learning - Jelena V. Pokimica; Lara A. Sinkovich (Inovacije u Nastavi)
In this scoping review, we have been guided by questions on the nature of the effects of Generative AI on lifelong learning in terms of its advantages and shortcomings, especially since the proliferation of AI technologies over the last half a decade. We have also highlighted major lifelong learning and artificial intelligence concepts discussed in literature, as well as reviewed current conceptual debates and tensions, while concentrating on higher education and work settings. Our findings are organized by three themes: 1) digitalization and technologication of lifelong learning; 2) self-directed learning, GAI and ChatGPT, and global contexts; and 3) human development and capability approach to lifelong learning. We draw on important implications for future empirical research directions, more fine-grained systematic reviews building on this preliminary work, and organizational considerations. We uniquely add to discussions of global perspectives in the realm of AI and lifelong learning and instigate probing into deeper human ontological processes behind learning.